RETRIBUSI ANGKUTAN UMUM PADA KANTOR PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KOTA SAWAHLUNTO - Annisa Arifka Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Public transportation is a transportation provided to the public that is paid for which the purpose is to transport people or goods from one place to another. Especially regarding public transportation to be able to carry out transport activities from one place to another, there needs to be a permit from the authorized agency. The procedure for collecting levies for general passenger transportation permit permits is based on the SPDORD as referred to in Article 12 paragraph (1) stipulated that levies are payable by issuing regional levies (SKRD) or other equivalent documents. For Sawahlunto City Regency, in accordance with Regional Regulation No. 11 of 1997 concerning Licensing for Public passenger transport routes, the tariff is classified into the type of public passenger transport and transport capacity. Basically, the obstacles faced in the issuance of public transportation route permit fees at the communications and information technology office of Limapuluh Kota Regency are the lack of knowledge of drivers in terms of issuance of public transportation route licenses, many employers who grant the requirements of public transport route licensing, and employers do not understand concerning the licensing of special routes for public transport